The Web Lift and Posterior Pull for the Aging Face - Ezzat, Waleed H.; Amodeo, Chiara Andretto; Keller, Gregory S. (Facial Plastic Surgery, 2012)
There are many factors that contribute to the aging neck. We have recently begun employing a percutaneous suture spanning the submentum combined with a posterior platysma pull. We present our initial results with this technique. In this retrospective study, subjects underwent the combined procedure with and without concomitant rhytidectomy. Cephalometric analysis was used to compare the preoperative cervicomental angle (CMA) and hyomental distance (HMD) with postoperative values at 4 weeks. Subjects also were queried on their postoperative satisfaction. Twenty-five subjects were included in this study. At 4 weeks postoperatively, we achieved significant reductions in the average CMA (134.8 versus 122.8, p = 0.002). The postoperative HMD significant increased an average of 1.9 cm (8.5 versus 10.4, p = 0.009). We achieved a 92.3% satisfaction score at 33 weeks (range = 25 to 44). The combination of a percutaneous suture across the submentum and a posterior platysma pull is a safe and effective method of addressing the many facets of the aging neck. Our initial results are easily reproducible and entail minimal morbidity to the patient.
Keywords: neck-lift; minimally invasive; rhytidectomy; aging face; platysmaplasty